For or Against the Eurozone? Romanian Students’ Perspective on the Economic Crisis and Their Future as European Citizens - MIHALCEA, Alina-Daniela; VIȚELAR, Alexandra; ANGHEL, Lucian Claudiu (Management Dynamics in the Knowledge Economy, 2014)
In the context of globalization and of the aftermath of the economic crisis, the pillars on which the EU stands no longer satisfy the demands and necessities of the European citizens (Van Ham, 2005; Habermas, 2012). The euro crisis has generated, on one hand, a gap between the “center” and the “periphery” that can be correlated with the fragmentation both of the EU’s spheres of influence and of the European financial market (Dobrescu & Palada, 2012; EFCR, 2013). On the other hand, the euro crisis has generated a lack of solidarity and confidence in the European project. At this point, the major challenge for the European Union is not only the Euro-zone crisis, but also the level of confidence amongst young people. Recent polls (Gallup, 2013; Pew Research Center, 2013) indicate a dramatic rise in pessimism among Europe’s young people that have been labeled as “the Lost Generation” (European Commission, 2012). This paper explores the impact of the economic crisis on Romanian students’ attitudes towards the future of the European project and towards their European identity. The study aims at identifying the major concerns of Romanian students in terms of their future as European citizens. Our approach of this subject covers two perspectives: the first one is the utilitarian perspective, that is taking into consideration the actual advantages of the Europeanization process and the sustainability of the European social and economic model in the current national economic context; the second one is the identity perspective, that is taking into account the impact of the economic crisis on the Romanian students’ sense of belonging to the European community. The results of our study indicate that, overall, the Romanian youth holds an optimistic view concerning the EU, however they express some concerns in terms of lack of solidarity and fear of national identity loss.